Effective Waterproofing of Railway Culvert Pipes - Liudmyla Trykoz; Svetlana Kamchatnaya; Oksana Pustovoitova; Armen Atynian; Oleksandr Saiapin (The Baltic Journal of Road and Bridge Engineering)
The composition material for waterproofing of the railway infrastructure objects, in particular, culvert pipes is suggested in the article. The waterproof composition contains an acrylic polymer and a filler. The comparison of the composition properties with two kinds of the fillers (silica sand and Portland cement) is carried out. The following properties are defined – water absorption, corrosion stability, stability in an aggressive environment, frost resistance to evaluating the suitability of the proposed composition for waterproofing. These properties are determined for three batches: an acrylic polymer without a filler, an acrylic polymer with silica sand, and an acrylic polymer with Portland cement. The test results show that the composition with silica sand possesses the best waterproofing properties. Wherein the quantity of silica sand is 1.5 mass parts to the quantity of polymer. Compared to the non-filled acrylic polymer the offered composition is characterised less water absorption, more significant corrosion stability and stability in an aggressive environment, better frost resistance. The mix with Portland cement shows a bit worse results at a higher cost of the material in whole.